Evaluasi Kinerja Operasional MRT Jakarta Menggunakan Big Data Pasca Covid-19 - Mira Lestira Hariani; Fariz Ramadhan (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
The performance of public transportation is a very important main indicator because it can represent the success of the implementation of public transportation. This study aims to determine the operational performance of the MRT Jakarta public transportation after Covid-19 based on passenger tapping data (big data) and user perceptions. This big data will be processed into an Origin - Destination matrix, to get the Load factor and Utilization Factor values. In this study, in assessing whether or not public transportation performance is good, we will use secondary survey data on public transportation performance standards from journals in providing MRT and LRT services in the cities of Singapore, Hong Kong, and the United States, which of course refers to the Decree of the Director General of Land Transportation in Indonesia (SK/687/AJ/DRJD/2002). The results of the study show that the operational performance of the Jakarta MRT is currently good from several factors based on users perception and standard used. The results of the analysis show that the MRT Jakarta average occupancy rate or load factor value is 67% and utilization factor value is 0,66, which means that the performance of MRT Jakarta from the ridership side is still not optimal.